Gastric adenomyoma: a case report - Bhardwaj, Sushma; Sinha, Shourabh; Kundu, Reetu; Kaur, Ravinder (International Surgery Journal, 2018)
Upper gastrointestinal (GI) bleeding is usually seen secondary to esophageal varices or peptic ulcer disease, but at times, unusual causes can be encountered. We present one such case of a young 30-year-old gentleman who presented with recurrent episodes of upper GI bleeding secondary to gastric adenomyoma (GA), a rare, benign gastric tumor that usually remains asymptomatic or presents with vague abdominal symptoms.